Social policy review. edited by John Hudson, Catherine Needham and Elke Heins. - Hudson, John, 1972-; Needham, Catherine, 1974-; Heins, Elke (Policy Press, 2017)
Published in association with the SPA, this edition presents an up-to-date and diverse review of the best in social policy scholarship over the past twelve months, from a group of internationally renowned authors.